La traduction comme OVNI - Nouss, Alexis (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractIn view of the shaky foundations of translation studies as a discipline, the author suggests an hermeneutic epistemology of translation. Of two possible approaches, which are described using the analogy of the "water diviner" (sourcier) and "well maker" (puisatier), the author opts for the former, and justifies his choice by defining translation as a transformation process, a primary, not secondary, language operation. He cites contemporary literary and philosophical theories to look at the issues of identity and alterity in translation, as well as the role of the history and the uncertainty of meaning. According to Nouss, translation is in essence an always Unidentifiable Flying Object (UFO).